The Influence of Economic Growth, Human Development Index and Unemployment on Poverty in Medan City - Harahap, Rona Riski; Ramadhan, Anggia; Fadlan, Ahmad (Holistic Science, 2025)
This study aims to analyze the influence of economic growth, the human development index, and the unemployment rate on poverty in Medan City from 2015 to 2024 using quantitative research methods through multiple linear regression analysis on secondary data from the Central Statistics Agency. The results indicate that partially, economic growth has no significant effect on poverty (Sig. 0.321 more than 0.05), as well as the Human Development Index (Sig. 0.087 more than 0.05) and unemployment (Sig. 0.706 more than 0.05). Simultaneously, these three variables also have no significant impact on poverty (Sig. 0.181 more than 0.05) with a coefficient of determination (R²) of 0.297, meaning they only explain 29.7% of the variation in poverty levels in Medan City. Therefore, it can be concluded that other factors outside the research model have a more dominant influence on the high poverty rate in Medan City during the study period.